2008
DOI: 10.1007/s11199-008-9502-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Sexual Prejudice and Sport Participation: Implications for Sexual Minorities

Abstract: Utilizing the compulsory heterosexuality framework, the purpose of this inquiry was to assess the influence of gender and sexual prejudice on decisionmaking within sport. In Study 1, responses from former and current athletes within the United States (N=229) indicated that prejudicial attitudes predicted unwillingness to participate when a coach was identified as gay or lesbian. A mixed-methods approach was used in Study 2 to assess the attitudes of American parents (N=76). Parent's prejudicial attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 51 publications
(128 reference statements)
1
39
1
3
Order By: Relevance
“…In regards to the current study, research suggests that sexual minorities are members of a devalued or stigmatized social group, and this is especially the case in sport contexts (Anderson, 2005(Anderson, , 2009Griffin, 1998;Krane & Barber, 2005;Sartore & Cunningham, 2009a, 2009b. As such, sport employees who are LGBT have oftentimes concealed their sexual orientation to "pass" as in-group (i.e., heterosexual) members (Krane & Barber, 2005).…”
Section: Theoretical Framework Social Identitymentioning
confidence: 86%
See 2 more Smart Citations
“…In regards to the current study, research suggests that sexual minorities are members of a devalued or stigmatized social group, and this is especially the case in sport contexts (Anderson, 2005(Anderson, , 2009Griffin, 1998;Krane & Barber, 2005;Sartore & Cunningham, 2009a, 2009b. As such, sport employees who are LGBT have oftentimes concealed their sexual orientation to "pass" as in-group (i.e., heterosexual) members (Krane & Barber, 2005).…”
Section: Theoretical Framework Social Identitymentioning
confidence: 86%
“…For instance, we are both members of the Allies group on campus, with Allies representing individuals "willing to provide a safe haven, a listening ear, and support for lesbian, gay, bisexual, and transgender people or anyone dealing with sexual orientation issues." We also conduct research aimed at understanding sexual prejudice Sartore & Cunningham, 2009a, 2009b, the experiences of sexual minorities (Melton &Cunningham,2012), and the ways in which sexual orientation diversity influences group and organizational outcomes (Cunningham, 2011, in press;Cunningham & Melton, 2011). This study represents a continuation of this research stream…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wider cultural shift has also affected athletes, as there is evidence that homophobia is declining somewhat among members of team sports (Southall et al 2006-as cited in Anderson 2008. In addition, Sartore and Cunningham (2009) found that college students who were former or current athletes were more, rather than less willing, to play for either a gay or lesbian. Thus, perhaps facing less homophobia, taken together these sorts of data support the idea, also advanced by others (e.g., Anderson 2005;Elling et al 2001;Hall and Richardson 1982), that sexual minorities, especially at younger ages, may play sports at the same rate as heterosexuals.…”
Section: Athletic Participation and Sexuality: A Brief Reviewmentioning
confidence: 99%
“…In many respects, the norms and traditions of sport reinforce and perpetuate notions of hegemonic masculinity (Connell, 1995;Sartore & Cunningham, 2009). The gendered discourses, policies, and belief systems in sport typically privilege men and disadvantage womenmaking it seem natural to view athletes who display ultra-masculine or ultra-competitive traits as superior (Messner, 2009).…”
mentioning
confidence: 99%